Activated protein C has a regulatory role in factor VIII function - Wilhelm, Amelia R; Parsons, Nicole A; Samelson-Jones, Benjamin J; Davidson, Robert J; Esmon, Charles T; Camire, Rodney M; George, Lindsey A (Blood, 2021)
Mechanisms thought to regulate activated factor VIII (FVIIIa) cofactor function include A2-domain dissociation and activated protein C (APC) cleavage. Unlike A2-domain dissociation, there is no known phenotype associated with altered APC cleavage of FVIII, and biochemical studies have suggested APC plays a marginal role in FVIIIa regulation. However, the in vivo contribution of FVIIIa inactivation by APC is unexplored. Here we compared wild-type B-domainless FVIII (FVIII-WT) recombinant protein with an APC-resistant FVIII variant (FVIII-R336Q/R562Q; FVIII-QQ). FVIII-QQ demonstrated expected APC resistance without other changes in procoagulant function or A2-domain dissociation. In plasma-based studies, FVIII-WT/FVIIIa-WT demonstrated dose-dependent sensitivity to APC with or without protein S, whereas FVIII-QQ/FVIIIa-QQ did not. Importantly, FVIII-QQ demonstrated approximately fivefold increased procoagulant function relative to FVIII-WT in the tail clip and ferric chloride injury models in hemophilia A (HA) mice. To minimize the contribution of FV inactivation by APC in vivo, a tail clip assay was performed in homozygous HA/FV Leiden (FVL) mice infused with FVIII-QQ or FVIII-WT in the presence or absence of monoclonal antibody 1609, an antibody that blocks murine PC/APC hemostatic function. FVIII-QQ again demonstrated enhanced hemostatic function in HA/FVL mice; however, FVIII-QQ and FVIII-WT performed analogously in the presence of the PC/APC inhibitory antibody, indicating the increased hemostatic effect of FVIII-QQ was APC specific. Our data demonstrate APC contributes to the in vivo regulation of FVIIIa, which has the potential to be exploited to develop novel HA therapeutics.